Pengaruh Teknik Ice Breaking (Mencairkan Suasana ) Terhadap Motivasi Belajar Siswa Kelas VIII di SMP Satu Atap Negeri 5 Pangururan Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Tahun Pelajaran 2023/2024 - Elisabet Lastri Tumangger; Rusmauli Simbolon; Masniar H. Sitorus; Senida Harefa; Grecetinovvitria Butarbutar (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The aim of this research is to determine the positive and significant influence of the Ice Breaking Technique on the Learning Motivation of Class VIII Students at One Roof Middle School Negeri 5 Pangururan in Christian Religious Education and Character Education Subjects for the 2023/2024 Academic Year. The research method used is a quantitative method with a pre-experimental design type in the form of a One Shot Case Study. The population is all 102 class VIII students at One Roof 5 Public Middle School in Pangururan for the 2023/2024 academic year and a sample of 41 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 28 items, namely 12 items for variable Negeri 5 Pangururan Subjects of Christian Religious Education and Character Education for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test, obtained a value of rxy = 0.456> rtable(α=0.05,n=41)=0.308. b) Testing a significant relationship obtained a value of tcount= 3.200> ttable (α =0.05, dk=n-2=39)= 2.021. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 20.8%. 3) Test the hypothesis using the F test to obtain Fcount> Ftable=( α =0.05, dk numerator k=15, dk denominator=n-2=41-2=39) namely 10.24>1.92. Thus Ha accepted and H0 rejected.